Shareholder Taxes in Acquisition Premiums: The Effect of Capital Gains Taxation - Ayers, Benjamin C.; Lefanowicz, Craig E.; Robinson, John R. (Journal of Finance, 2003)
Abstract We exploit cross‐temporal differences in capital gains tax rates to test whether shareholder‐level capital gains taxes are associated with higher acquisition premiums for taxable acquisitions. We model acquisition premiums as a function of proxies for the capital gains taxes of target shareholders, taxability of the acquisition, and tax status of the price‐setting shareholder as represented by the level of target institutional ownership. Consistent with a lock‐in effect for acquisition premiums, results suggest a unique positive association between shareholder capital gains taxes for individual investors and acquisition premiums for taxable acquisitions, which is mitigated by target institutional ownership.